“AND WE WERE, ARE AND WILL ALWAYS BE” (MYKOLA NEVYDAILO’S PROPHETIC “PRYNOSYNY”) - Zaidler, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The creative work of Mykola Nevydailo, a prose writer from Dnipropetrovs’k, is researched. The peculiarities of his fictional thinking are revealed, the writer’s prose is introduced into the contemporary Ukrainian literary process.